2018
DOI: 10.1186/s12544-018-0292-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilitarian and hedonic walking: examining the impact of the built environment on walking behavior

Abstract: Introduction: Most previous studies have mainly focused on utilitarian or recreational walking and discussed their relationship with the built environment. The point is that most of these studies have not been sensitive to the motivation of trips while travel is a complicated behavior and individuals may have different degrees of motivation and utility for a given trip purpose. Accordingly, because of different utilities of travel, it is more likely that the built environment differently affects walking behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 69 publications
3
14
0
3
Order By: Relevance
“…In this study, utilitarian walking was associated with various individual and geographic variables, confirming previous findings in this domain [57,74,75]. In our study, females were found to be more likely to walk than males.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, utilitarian walking was associated with various individual and geographic variables, confirming previous findings in this domain [57,74,75]. In our study, females were found to be more likely to walk than males.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, perceived availability of sidewalks/shoulders (OR = 1.49, p = 0.098) which approached the significant level is relevant to pedestrian safety. This finding is consistent with previous studies reporting environmental factors associated with utilitarian walking in neighborhoods, in which safety has been one of the most frequently documented domains of correlates (9,40,41). Furthermore, older adults are more vulnerable to safety-related environmental challenges due to their functional and cognitive declines (28), and therefore providing safe and barrier-free environments may hold even greater importance to support their walking.…”
Section: Discussion and Conclusion Older Adultssupporting
confidence: 91%
“…Additionally, the built environment has an effect on the amount of walking, through variables such as mixed land use, aesthetics and walking infrastructure (e.g. [6,35,42]).…”
Section: Introductionmentioning
confidence: 99%